Protection from the lie and protection of truth between philosophy and law - Del Bò, Corrado (Governare la paura. Journal of interdisciplinary studies, 2019)
In the era of fake news, truth has become a different and more urgent political problem than the traditional issues of the arcana imperii and the lies of the rulers. Starting from this observation, and deepening some considerations contained in the essay by Hannah Arendt Thruth and Politics, the article offers a worried report on the possibility of truth (scientific and factual) not to be reduced to mere opinion among others, and concludes that only a loyal collaboration between epistemic authorities and politics can make the judicial road for the protection of truth less attractive.